Uji Aktivitas Antioksidan dan Daya Terima Es Krim Ekstrak Daun Sambiloto (Andrographis paniculata (Burm. f) Nees) - Nita Maylina; Afrinia Eka Sari (HB PRESS, 2023)
One of the antioxidants that can increase the body's immunity is bitter leaf (Andrographis paniculata (Burm. f) Nees). This leaf is rarely used. Therefore, it is used with more interesting processing such as ice cream. This study was to determine antioxidant activity, overrun, melting speed, organoleptic characteristics and preference level of the ice cream of bitter leaf extract. Method is Completely Randomized Design (CRD). There were 3 treatments, namely 8%, 16% and 24% of bitter leaf extract. The results of the antioxidant activity test on the ice cream of bitter leaft extract, the three formulas have a very weak antioxidant content. The highest overrun ice cream test results, namely formula 3 50%. The results of the ice cream melting speed test on the three formulas still do not meet the standards for a good ice cream melting speed. The results of statistical test analysis on indicators of color, aroma, taste and texture showed there was a significant difference from the statistical test results obtained p-value <0.05. The most preferred level of preference for bitter leaf extract ice cream was formula 1. It could be concluded that the bitter leaf extract ice cream was acceptable to the public.